Teaching and Learning Strategies of Reading Comprehension Skill for Asian Countries Students - Maria Gaudensia Wilhelmina Bria (Indonesian EFL Journal: Journal of ELT, Linguistics, and Literature, 2018)
This study focus on how the senior high school students in the Asian countries learning English as a second language, explore their comprehension in reading skill. There are some factors mentioned about how the application in reading comprehension skill have main important role in studying and learning English as a second language and learning another subjects. The skills in reading comprehension; knowing and understanding the vocabularies, skill coding, the preparation contextual materials or modules must be appropriate and suitable with the situation and back ground of the country which are learning English as a second language taking place. How the learning strategies influence the English learning especially in reading skill by focussing on the learning strategies of female and male and how this skill in learning English influence the students’ performance science in their school. With all these reasons it will be summarized with Langan’s numeration about how to have a good reading comprehension in eight skills mentioned and there are some skills related to these journals taking from five Asian countries will be analysed.